ATP12A Proton Pump as an Emerging Therapeutic Target in Cystic Fibrosis and Other Respiratory Diseases - Michał Dębczyński; Giulia Gorrieri; Damian Mojsak; Floriana Guida; Federico Zara; Paolo Scudieri (Biomolecules, 2023)
ATP12A encodes the catalytic subunit of the non-gastric proton pump, which is expressed in many epithelial tissues and mediates the secretion of protons in exchange for potassium ions. In the airways, ATP12A-dependent proton secretion contributes to complex mechanisms regulating the composition and properties of the fluid and mucus lining the respiratory epithelia, which are essential to maintain the airway host defense and the respiratory health. Increased expression and activity of ATP12A in combination with the loss of other balancing activities, such as the bicarbonate secretion mediated by CFTR, leads to excessive acidification of the airway surface liquid and mucus dysfunction, processes that play relevant roles in the pathogenesis of cystic fibrosis and other chronic inflammatory respiratory disorders. In this review, we summarize the findings dealing with ATP12A expression, function, and modulation in the airways, which led to the consideration of ATP12A as a potential therapeutic target for the treatment of cystic fibrosis and other airway diseases; we also highlight the current advances and gaps regarding the development of therapeutic strategies aimed at ATP12A inhibition.